Ansiedad y depresión en alumnos de la carrera de medicina de la Universidad Nacional de Loja - Aldaz Albán, Abel Alejandro (2023)
Anxiety and depression are mental disorders that affect the mental health and psychosocial balance of people, especially in medical students who face a lot of stress. The purpose of the study was to determine the degree of anxiety and depression associated with mood in medical students at the National University of Loja. A cross-sectional descriptive quantitative study was carried out with a sample of 156 medical students. The Hamilton Scale, the Beck Inventory and the Mood Rating Scale were applied. It was found that 26.28% of the students had a level of anxiety, being more frequent in women between 20 and 24 years old. Minimal depression was reported in 59.62% of students, with a higher prevalence in women between 20 and 24 years old. 60.26% of the students had a happy mood, mainly women between 20 and 24 years old. Through the chi square analysis, a significant relationship was found between mood and anxiety, as well as between mood and depression, where negative mood states were associated with higher levels of depression. There is a positive relationship between mood states and anxious and depressive disorders in medical students at the National University of Loja. Mood appears to influence the levels of anxiety and depression experienced. These findings are important to improve attention to students' mental health